Case series report: use of vibroacoustic pulmonary therapy in patients with thoracic trauma complicated by acute respiratory failure - Konkayev, Aidos; Bekniyazova, Assema; Khamidullina, Zaituna; Konkayeva, Maiya (Frontiers in Medicine, 2024)
Chest injury is often accompanied by polytrauma and is complicated by respiratory failure. This article presents a series of cases with verified acute respiratory failure in patients with chest injury, where vibroacoustic pulmonary therapy was used in complex treatment. Dynamic X-rays and respiratory drive indicators reflected the effect of the use of vibroacoustic lung therapy. Early diagnosis of respiratory disorders and complex therapy using vibroacoustic pulmonary therapy can improve results. As a result, the time spent in the hospital and in the intensive care unit is reduced, and the frequency of adverse outcomes is reduced.